Nonalcoholic Steatohepatitis in Bariatric Patients with a Diagnosis of Obstructive Sleep Apnea - Weingarten, Toby N. (Obes Facts, 2012)
OBJECTIVE: To study a possible association between obstructive sleep apnea (OSA) severity, managed with noninvasive ventilation, and nonalcoholic steatohepatitis (NASH) in bariatric surgical patients. METHODS: Medical records of 218 bariatric surgical patients who underwent liver biopsy were reviewed. OSA severity was determined from preoperative polysomnography (apnea-hypopnea index (AHI) ≤ 15 no/mild OSA vs. AHI ≥ 16 moderate/severe OSA). Patients diagnosed with OSA were prescribed noninvasive ventilation. Patients were categorized according to liver histopathology into 3 groups: i) no liver disease or simple steatosis, ii) mild NASH (steatosis with necroinflammation and mild fibrosis (stage 0–1)), and iii) advanced NASH (steatosis with necroinflammation and more advanced fibrosis (stage ≥ 2)). RESULTS: 125 patients (57%) had no/mild OSA, and 93 (43%) had moderate/severe OSA. There was no difference in serum aminotransferases between patients by OSA severity classification. There was a high prevalence of hepatic histopathological abnormalities: 84% patients had steatosis, 57% had necroinflammation, 34% had fibrotic changes, and 14% had advanced NASH. There was no association between severity of NASH and severity of OSA. CONCLUSIONS: There is no association between stage of steatohepatitis and OSA severity among morbidly obese patients managed with noninvasive ventilation.